Belajar bahasa inggris di komunitas lokal - Ella, Ella; Rahmat, Rahmat; Rahmiani, Nur (Al-Aqad, 2025)
This study aims to examine the practice of ijarah (leasing) in rental housing agreements and to analyze such practice based on the Compilation of Sharia Economic Law (KHES), specifically regarding ijarah contracts for rental houses built on land owned by a third party. The research employs a qualitative method with a field study design and an empirical approach. Primary data were collected through interviews with ten informants—five landlords and five tenants—in the Waduk Permai area of Pontianak City. Secondary data were obtained from books and journals to support and strengthen the findings. Data collection techniques included interviews and documentation, and data validity was ensured through triangulation. The findings show that: 1) Rental agreements for houses in Waduk Permai are conducted orally, without any written contract or formal written ijarah agreement. The researcher also found that landlords did not clearly disclose at the outset of the agreement that the land under the rental house was not their own property. 2) According to KHES Article 303, the lessor in an ijarah contract must be the owner of the property, their authorized representative, or a legal guardian. However, in the observed cases, the lessors did not meet any of these conditions stipulated in KHES Article 303, raising concerns about the validity of the ijarah contracts in this context.